PERAN KONTEN FOREX DALAM MEMBENTUK CITRA POSITIF TRADING FOREX STUDI KASUS PADA CNBC INDONESIA - Novriansyah P, Alfredo; Yuliani, Hafri (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
This research aims to analyze the content of content about foreign exchange (forex) trading published on CNBC Indonesia media regarding the role of this content in forming a positive image regarding forex trading activities. The method used is descriptive qualitative using Content Analysis theory from Roland Barthes. Data was collected through collecting videos from forex news programs on the CNBC Indonesia YouTube channel and then transcribed into text form to be used as an object of analysis. This research shows that the forex content presented by CNBC Indonesia plays an important role in forming a positive image of forex trading among the public. Through the forex trading news program and coverage of the Trader Family forex education event, CNBC Indonesia provides comprehensive information about the process of becoming a customer and how to carry out forex trading transactions, as well as providing simple forex trading tips that emphasize the importance of risk management to achieve success in forex trading. Apart from that, the research results show that the content on Prevent Forex Fraud and Trader Family Education for Thousands of People which was covered by Shania Alatas, a CNBC Indonesia journalist, also made a positive contribution in forming a positive image regarding forex trading. In the context of Roland Barthes' content analysis, the messages conveyed in the news can be seen as mythological messages that form a positive image about forex trading. Therefore, it can be concluded that the forex content presented by CNBC Indonesia has an important role in forming a positive image regarding forex trading, providing accurate and complete information, and increasing public confidence in forex trading as a safe and reliable investment product. Keywords: Content analysis, Forex trading, Positive image of forex trading